Implementation of Blockchain Technology in Improving Transparency of Public Services: A Case Study on Government Service Delivery in Indonesia - Judijanto, Loso (West Science Information System and Technology, 2023)
This research investigates the implementation of blockchain technology in enhancing the transparency of government service delivery in Indonesia through a quantitative analysis. Utilizing a mixed-methods approach, including regression analysis, descriptive statistics, and demographic analysis, the study explores the perceptions of government officials, service providers, and citizens regarding the impact of blockchain adoption. The findings reveal overwhelmingly positive perceptions, with statistically significant relationships identified between blockchain adoption and perceived transparency, user satisfaction, reduced incidents of corruption or fraud, and improved time and cost efficiency. The demographic analysis highlights variations in perceptions across different stakeholder groups, emphasizing the need for tailored approaches in policy formulation. These results contribute to the evolving discourse on blockchain technology in the public sector, providing valuable insights for policymakers and practitioners.